Rola służb specjalnych w demokratycznym państwie prawa - Grochowski, Robert (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
The name of special services is applied to the civil and military services that orga-nize and conduct intelligence and counterintelligence activities. Their operations are an element generating social and political trust between the political authorities and citizens. Given the current conditions of international relations and the international situation, a state is required to have efficient special services at its disposal. A negative impact of globalization on state functioning, both in its external and in-ternal dimensions, forces Polish special services to strengthen their fundamental func-tion, that is providing information. The weakness of military intelligence and counterintelligence follows from the dissolution in 2000 of the Military Intelligence Services (WSI), and wasting their potential for political reasons. The role and task of special services in a democratic state should be to protect the liberty and democracy of the political system’s principles, as set out in the Constitution, instead of protecting particular interests. The nature of the transformations occurring in security circles in Poland and related globalization processes, as well as civilizational, cultural and tech-nological changes and the emergence of a civil society, demand a different attitude to the special services to be taken both by the public authorities and society, and make changes in their functioning necessary. This also calls for the need for a theoretical in-terpretation of the operations of modern Polish special services in a democratic state of law.
The role of special services in a democratic state of law